Activity enhancement upon the incorporation of titanium: au@ti-sio2 core-shell nanocatalysts for the CO oxidation reaction - Sekhar, Anandakumari C. Sunil; Kottavarithottil Ziyad; Soni, Yogita; Vinod, Chathakudath P. (ChemCatChem, 2015)
The encapsulation of gold nanoparticles 8-12nm in size within a porous Ti-SiO2 shell to form a core-shell nanoarchitecture was investigated, and the catalytic activity of the resulting structure was probed. Detailed characterization of the synthesized materials shows that the core-shell morphology is lost beyond a certain amount of incorporated titanium, and results in normal gold-supported Ti-SiO2. The material has a high surface area (913m(2)g(-1)) and high porosity, both of which make it an excellent choice for catalytic applications. With the optimum amount of incorporated Ti, the core-shell catalyst shows excellent room-temperature CO oxidation activity over several cycles with retention of its morphology at higher temperatures.
Keywords: core-shell structures; gold nanoparticles; Oxidation; Ti-SiO2

Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis